2019
DOI: 10.1002/imhj.21831
|View full text |Cite
|
Sign up to set email alerts
|

Cognitively‐Based Compassion Training for parents reduces cortisol in infants and young children

Abstract: This study tests a group‐based secular contemplative practice intervention, Cognitively‐Based Compassion Training (CBCT), with parents of young children. We report on a randomized controlled preliminary efficacy study. Certified teachers administered CBCT for 20 hr across 8 to 10 weeks in two cohorts of parents with infants and young children. The intervention group was compared to a waitlist control group. Thirty‐nine parents and their children, who ranged in age from 4 months to 5 years, were evaluated at pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 94 publications
0
7
0
1
Order By: Relevance
“…In the study by Fisher and colleagues, there was a decrease in the mean cortisol level of the caregivers who participated in the intervention [ 40 ]. One other study measured hair cortisol in children and the results showed that the cortisol concentration was lower in the intervention group compared with the controls [ 49 ]. Because hair cortisol measures evaluate the average level of cortisol over several months prior to the sample being taken, these results were not comparable to the other studies included in the review (based on saliva and urine samples), and so could not be included in the meta-analysis [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study by Fisher and colleagues, there was a decrease in the mean cortisol level of the caregivers who participated in the intervention [ 40 ]. One other study measured hair cortisol in children and the results showed that the cortisol concentration was lower in the intervention group compared with the controls [ 49 ]. Because hair cortisol measures evaluate the average level of cortisol over several months prior to the sample being taken, these results were not comparable to the other studies included in the review (based on saliva and urine samples), and so could not be included in the meta-analysis [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…That approach, a proxy measure of the HPA axis activity over the previous months, evaluates chronic stress, which is less influenced by immediate variables, and may better capture parenting intervention effects not seen in the studies reviewed here [ 61 , 62 ]. The single study using this method found that parent-training intervention can reduce chronic cortisol levels [ 49 ]. The use of markers like hair samples of cortisol in future studies might better represent the chronic stress that is considered so toxic for human functioning and development.…”
Section: Discussionmentioning
confidence: 99%
“…At the householdlevel, parent-child interventions that promote supportive parenting styles or social cohesion during times of instability and/or heightened parental stress may help to foster resiliency in children 78,79 . In fact, parenting interventions that focus on maternal responsiveness have revealed measurable biological impacts on children's genome-wide DNAm profiles 80 and on other biomarkers [81][82][83] . At the neighborhood-level, after-school programs, community recreational centers, or other community-based interventions 65 that provide added support/routine to children's environments might be particularly beneficial to children whose families are experiencing socioeconomic instability.…”
Section: Discussionmentioning
confidence: 99%
“…We computed the a priori power using G*Power 3.1 [ 36 ] based on a repeated measures MANOVA with two outcome variables, an α = 0.05 and an effect size of f = 0.37, based on the effect size of Poehlmann-Tynan et al [ 17 ]. With a sample size of 798 (both cohorts, sample size at T4), the a priori power was excellent (0.99) for detecting main effects.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, only chronic stress indicated by long-term deviations in cortisol levels as assessed with HCC across several months may be problematic [ 16 ]. To our knowledge, only one small RCT including 25 parents and their children investigated the effect of compassion training in parents on children’s HCC and found decreased HCC in the intervention group [ 17 ].…”
Section: Introductionmentioning
confidence: 99%